Beta vulgaris as a natural nitrate source for meat products: A review - Munekata, Paulo E. S. (2021)
Curing meat products is an ancient strategy to preserve muscle foods for long periods. Nowadays, cured meat products are widely produced using nitrate and nitrite salts. However, the growing of the clean-label movement has been pushing to replace synthetic nitrate/nitrite salts (indicated as E-numbers in food labels) with natural ingredients in the formulation of processed foods. Although no ideal synthetic nitrate/nitrite replacements have yet been found, it is known that certain vegetables contain relevant amounts of nitrate. Beta vulgaris varieties (Swiss chard/chard, beetroot, and spinach beet, for instance) are widely produced for human consumption and have relevant amounts of nitrate that could be explored as a natural ingredient in cured meat product processing. Thus, this paper provides an overview of the main nitrate sources among Beta vulgaris varieties and the strategic use of their liquid and powder extracts in the production of cured meat products.